2002
DOI: 10.1590/s0004-27302002000200006
|View full text |Cite
|
Sign up to set email alerts
|

Tireoidite de Hashimoto na Infância e na Adolescência: Estudo Retrospectivo de 43 Casos

Abstract: A tireoidite de Hashimoto (TH) é uma doença auto-imune considerada a principal causa de bócio e hipotireoidismo adquirido em crianças e adolescentes em áreas não endêmicas. Este estudo avaliou retrospectivamente 43 pacientes entre 1,1 e 17,6 anos com TH, 36 do sexo feminino e 7 do sexo masculino (proporção 5:1). Destes, 81% apresentavam bócio. Na avaliação inicial 37% dos pacientes eram eutireóideos (n=16), 28% apresentavam hipotireoidismo compensado (n=12), 26% hipotireoidismo descompensado (n=11) e 9% eram h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
1
0
3
Order By: Relevance
“…In the present study, the prevalence of AITD was 21%, within the range found in other studies in the same age group, from 12.8% to 25.5% [8][9][10][11][12][13][14]. If we compare our data to other national studies on pediatric population, we found only one with a bigger number of patients, who studied 383 (9 months to 25 years of age) diabetic patients, in a different area of Brazil.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the prevalence of AITD was 21%, within the range found in other studies in the same age group, from 12.8% to 25.5% [8][9][10][11][12][13][14]. If we compare our data to other national studies on pediatric population, we found only one with a bigger number of patients, who studied 383 (9 months to 25 years of age) diabetic patients, in a different area of Brazil.…”
Section: Discussionsupporting
confidence: 84%
“…A tireoidite de Hashimoto ou tireoidite linfocítica crônica é uma doença autoimune caracterizada por infiltrado linfo-plasmocitário no parênquima tireoidiano, elevação do hormônio tireoide-estimulante, e diminuição dos hormônios tireoidianos (T3 e T4) 4,5,11,12,13 .…”
Section: Introductionunclassified
“…A tireoidite de Hashimoto resulta da incapacidade dos linfócitos T supressores em destruir clones de linfócitos sensibilizados por antígenos tireoidianos, com consequente citotoxicidade mediada por células natural killer e interação de linfócitos T auxiliares com linfócitos B, produzindo anticorpos contra componentes tireoidianos 11,12 . Células da tireoide de pacientes com tireoidite de Hashimoto não são individualmente normais, expressam alterações de genes, entre eles: ET/PTC, RAS e FAS; este, implicado como mediador da morte das células apoptóticas, levando à depleção dos folículos, ao hipotireoidismo e ao processo destrutivo 11,13,14 .…”
Section: Introductionunclassified
“…Thus, caution is recommended in relation to the indication of levothyroxine replacement therapy (22), since monitoring of these patients showed long-term, low risk of progression to HT. Repeated clinical and laboratory evaluation is necessary for correct indication of treatment in DS patients who have TSH-nd.…”
Section: Discussionmentioning
confidence: 99%